Behaviour of steel columns with realistic boundary restraints under standard fire. (December 2020) - B.D., Rakshith; M., Suneel Kumar
Abstract: The significance of the occurrence of linearly varying rotational restraint with an increase in temperatures during building fires is outlined. A detailed parametric study conducted on seven hundred and twenty specimens using ABAQUS® investigates the effect of linearly varying rotational restraint on the stability of steel columns under standard fire was presented. Surface plots are drawn to understand the interactive effect of slenderness ratio of a column, axial boundary restraint, and temperature (buckling and critical) with linearly varying rotational restraint for different pre-applied axial load and moment ratios. The prevalence of axial force (Pbuckle /PO ) at the ends of the columns due to axial restraint against thermal expansion is also assessed and plotted for the above parameters considered. It was found that buckling temperature and buckling load decreases with an increase in pre-applied axial load and moment while critical temperature variation was insignificant. The interaction equation useful for designers is proposed based on the non-linear regression analysis for assessing the critical temperature of steel columns under standard fire. It was found that the Euro code interaction equation (Eq. 4.21) predicted the critical temperature of a column with varying rotational restraint with reasonable accuracy.